Treatment outcome among children under-five years hospitalized with severe acute malnutrition in St. Mary's hospital Lacor, Northern Uganda. Issue 1 (December 2016) - Nyeko, Richard; Calbi, Valeria; Ssegujja, Boniface; Ayot, Grace
Abstract Background Severe malnutrition contributes to more than 60 % of deaths in children in developing countries. The minimum international standard set for management of severe acute malnutrition is a cure rate of at least 75 % and death rate of less than 10 %, yet the outcome of severely malnourished children treated in most hospitals in developing countries remain poor. This study was conducted to determine the treatment outcomes among severely malnourished children admitted at St. Mary's hospital Lacor in Northern Uganda during a one year period in order to inform clinical decisions to maximize management of severely malnourished children. Methods This was a retrospective study involving 251 severely malnourished children treated at St. Mary's hospital Lacor within a one year period in 2014. Patients' medical records in the facility therapeutic feeding unit were retrospectively reviewed using a check list to collect basic demographic, clinical, and treatment outcome data of the sampled study patients. The UNICEF treatment outcome categories were used, and further grouped into three summary categories: "successful (cured)", "died" and "potentially unsatisfactory". Data were entered, cleaned and analyzed using statistical package SPSS version 13. For categorical data, proportions with 95 % confidence intervals, odds ratio and Chi-square test to compare different groups were used. Multivariate analysis using logistic regression was used to analyze the association between treatment outcome and potential associated factors. P values less than 0.05 was considered for statistical significance. Results The study consisted 251 patients and the treatment outcome was successful (cured) in 168 (66.9 %) and potentially unsatisfactory in 53 (21.2 %), while 30 (11.9 %) died. Hypothermia and HIV infection were the factors significantly associated with mortality among the severely malnourished children in the current study. Conclusions The treatment cure rate of severely malnourished children admitted at St. Mary's hospital Lacor of 66.9 % is below the accepted standard of least 75 % cure rate. A high proportion of patients died (11.9 %) or defaulted (8.0 %). Hypothermia and HIV infection were the factors significantly associated with mortality. We recommend that in order to address the high default rate, home based care through the outpatient therapeutic care should be strengthened.